Sustainability of Audit Profession in Digital Technology Era: The Role of Competencies and Digital Technology Capabilities to Detect Fraud Risk - Fazlida Mohd Razali; Norhayati Sulaiman; Dewi Izzwi Abdul Manan; Jamaliah Said (SAGE Open)
Fraud constitutes a significant and pervasive risk within the broader landscape of cybercrime, driven by the rapid evolution of digital technologies. The work of an external auditor in evaluating fraud risks is frequently being judged. This is especially true when many legal actions are taken against auditors who fail to discover financial account manipulations, misstatements, misconducts, and standard non-conformance. Failure to discover these issues led to massive financial losses to corporations, as happened to Satyam Computers Limited. Numerous studies have investigated the factors influencing auditors’ efficiency in their work, but studies on the digital technology capability of auditors focusing on Malaysian auditors have been very much neglected. With the function of technology as the enabler of business operations nowadays, the ability to use technology is crucial regardless of profession. Hence, there is a need to assess whether digital technology capability could strengthen the relationship between external auditors’ efficiency and competence in assessing fraud risks. To prove this relationship, 455 questionnaires were distributed to members registered under the Malaysian Institute of Accountants working as external auditors. Based on the analysis of 150 responses through PLS-SEM, this study confirmed that external auditors’ effectiveness is enhanced if they are skillful in using audit software to plan and manage audit processes, organize and distribute audit information, analyze audit data, and run audit quality programs. With proficiency in utilizing digital technology, an external auditor tends to outperform others who are not in terms of fraud risk assessment. Therefore, it can be deduced that digital technology skills are vital to auditors. The skills should be acquired at higher learning institutions and further developed at audit firms to ensure the relevance and sustainability of the audit profession in the era of digitalization.